2013
DOI: 10.2196/jmir.2421
|View full text |Cite
|
Sign up to set email alerts
|

Online Social Network Use by Health Care Providers in a High Traffic Patient Care Environment

Abstract: BackgroundThe majority of workers, regardless of age or occupational status, report engaging in personal Internet use in the workplace. There is little understanding of the impact that personal Internet use may have on patient care in acute clinical settings.ObjectiveThe objective of this study was to investigate the volume of one form of personal Internet use—online social networking (Facebook)—generated by workstations in the emergency department (ED) in contrast to measures of clinical volume and severity.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…The use of smartphones to engage in personal Internet use in hospitals is becoming increasingly prevalent (Black et al . ). There is an increasing awareness that some smartphone uses, even those that are self‐initiated, can be distracting and detrimental (Rivera‐Rodriguez & Karsh ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The use of smartphones to engage in personal Internet use in hospitals is becoming increasingly prevalent (Black et al . ). There is an increasing awareness that some smartphone uses, even those that are self‐initiated, can be distracting and detrimental (Rivera‐Rodriguez & Karsh ).…”
Section: Resultsmentioning
confidence: 97%
“…investigated the impact of non‐work related Internet use on patient care in clinical settings (Black et al . ). They found that Facebook use made up a substantive percentage of clinician time, and that social media use increased with patient volume and acuity within the emergency department, suggesting that employees use smartphones to take breaks from a stressful environment.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…19 Now that social media is so prevalent and available at our fingertips, it can be accessed anywhere, including hospitals and clinics. Being able to be on Facebook so much could prove to be a distraction from patients and proper patient care.…”
Section: Risks To Privacymentioning
confidence: 99%
“…19 This is not just access by lower-level employees either-higher-status employees are actually shown to have a higher personal use of social media in the workplace. 20 This shows that personal social media usage is rampant through all tiers of health care provision.…”
Section: Risks To Privacymentioning
confidence: 99%